How to read a film - Monaco, James; Harbor Electronic Publishing; UNET 2 Corporation; Oxford University Press (Oxford : Oxford University Press, 2000)
Discusses more on producing a motion pictures
Multimedia edition depends on two standard pieces of software which is Adobe Acrobat and QuickTime
Keywords: Motion pictures; Motion pictures -- Study and teaching